Pensar biologicamente é pensar evolutivamente: jogo didático como facilitador da aprendizagem dos conhecimentos em biologia evolutiva e seleção natural, com base na teoria da aprendizagem significativa - Alencar, Elaine Paula Gonçalves (2019)
Considering evolution as a central and guiding axis of all areas of the biological sciences, this study discussed the importance of using students' prior knowledge in teaching practice, based on the theoretical principles of meaningful learning. The great challenges of the teaching of evolution are the historical duel science versus religion, the misconceptions about the randomness of mutations and the lack of knowledge of the real mechanism of natural selection. The aim of this work is to enable the construction of an evolutionary look at biology for students, from their personal experiences. The applied methodology was a didactic strategy that included a guided tour of a preserved Caatinga environment and the application of the board game “thinking biologically is thinking evolutionarily”, which simulated population changes in rattlesnakes in different Caatinga environments. The final sample consisted of 78 students of the 3rd year of high school, divided into control and experimental groups. Data were collected through questionnaires, photographic records made by students and written reports about each step of the methodology. The results, after qualitative and quantitative analysis, allowed us to conclude that there was a better understanding of the mechanisms of evolution, especially the adaptations of the Caatinga living beings, such as the lizard`s camouflage. There was a 24% increase in satisfactory responses from the experimental group over the control group regarding the rarity of albino rattlesnakes. Other aspects of the theory, especially those involving human evolution, need to be reinforced through specific strategies. It is concluded that the didactic teaching strategy used here is adequate to be applied to the real-life learning situations of the students of the sample, but the ideal method is an evolutionary approach to all the contents of biology from the first year of this stage of teaching.